EXPLORING THE IMPACT OF SELFEDUCATION ON THE PROFESSIONAL GROWTH OF MEDICAL STUDENTS - Lutfullayeva Khulkarkhon Asatullaevna (Western European Studies, 2024)
The article focuses on the issue of self-education among medical students in English classes with a professional focus. Its objective is to explore a pedagogical approach for enhancing the self-educational skills of medical university students through the development of Englishlanguage professional competence. The article draws on methodologies outlined in educational concepts such as those by UNESCO, the Bologna process, WFME, program documents on education in Uzbekistan, state standards on medical education, as well as research-theoretical, research, and practice-based methods. The pedagogical system presented in the article addresses students' self-educational activities in the context of studying English with a professional orientation. It establishes a diagnostic system for assessing the level of selfeducational skills among future specialists, which has been applied in practice. The article proposes an improved methodology for teaching English that combines various pedagogical technologies aimed at fostering universal educational actions, motivating learning, developing students' self-educational skills, and enhancing their proficiency in foreign professional terminology, as well as communicative and research skills in English. The experimental group of students demonstrated better outcomes compared to the control group in terms of selfeducational activities and proficiency in English-language professional terminology, as well as communicative and research skills in English
Keywords: Self-education; medical students; foreign professional competence; diagnostics